2018
DOI: 10.1200/jco.18.00138
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Transformation to Higher-Grade Lymphoma and Its Impact on Survival in a Large Cohort of Patients With Marginal Zone Lymphoma From a Single Institution

Abstract: Purpose Given the paucity of data on higher-grade transformation (HGT) to aggressive lymphoma in patients with marginal zone lymphoma (MZL), we report on a large cohort of patients, identify risk factors, and determine HGT impact on overall survival (OS). Methods We analyzed 453 patients with biopsy-proven MZL seen at our institution between 1995 and 2016. Kaplan-Meier, Cox proportional hazards regression, and competing risk methods were used in analyses of time-to-event outcomes. Results Thirty-four patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
73
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 57 publications
(87 citation statements)
references
References 32 publications
9
73
5
Order By: Relevance
“…Similar to previous studies, all patients, including those with early‐stage disease, face a continuous risk of relapse. This indicates that EMZL should be followed indefinitely . We confirmed that higher IPI, FLIPI, and MALT‐IPI scores predict shorter survival in EMZL patients in multivariable Cox regression models, with MALT‐IPI carrying the highest HR.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similar to previous studies, all patients, including those with early‐stage disease, face a continuous risk of relapse. This indicates that EMZL should be followed indefinitely . We confirmed that higher IPI, FLIPI, and MALT‐IPI scores predict shorter survival in EMZL patients in multivariable Cox regression models, with MALT‐IPI carrying the highest HR.…”
Section: Discussionsupporting
confidence: 72%
“…However, another study did not show such an association . Higher grade transformation (HGT) has been reported in patients with EMZLs at an incidence of 3.8% to 13% . However, whether the incidence of HGT is higher in patients with MMS and varies by EMZL location at presentation remains unknown.…”
Section: Introductionmentioning
confidence: 98%
“…While this manuscript was in preparation, another retrospective study was published, which examined the occurrence of high‐grade transformation in MZL and its effects on subsequent PFS and OS . The authors demonstrated that dichotomized IPI, FLIPI, and MALT‐IPI scores are predictive of shorter PFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…Since PVRL cells rapidly die once they leave the eye, it is critical to process the specimen promptly. PVRL is almost always a diffuse large B cell lymphoma (DLBCL) although T cell lymphomas and marginal zone lymphomas have also been reported …”
Section: Introductionmentioning
confidence: 99%